Morphofunctional transformation of pancreatic islets in immature rats on the 70-th day of experimental diabetes - Miskiv , Vasyl; Kogut , Anna; Zhurakivska , Oksana; Kulinich-Miskiv , Mariana; Antimis , Olga; Dutchak , Ulyana; Hrechyn , Andriy; Pertsovich, Vasyl (The Ukrainian Scientific Medical Youth Journal, 2025)
in studies conducted on animals using histological and electron-microscopic methods of study, analysis of the peculiarities of the reconstruction of pancreatic islets in 3-month-old rats on the 70-th day of the course of experimental diabetes was carried out. Because this period of diabetes in rats is a critical time to study morphofunctional changes, especially in immature rats, where the endocrine and metabolic systems are still developing and interacting with diabetes-induced changes. Ultrastructural features of the pancreas were studied under a РEM-125 K electron microscope at an accelerating voltage of 75 kV. Microphotography of the sample was performed using a Leica DM 750 light microscope and photographed using a digital SSD camera (Industrial digital camera UHCCD05100KPA-U-NA-N-C-SQ-NA). Morphometry was performed on micropreparations using the Bio Vision 4.1 program in automatic or manual mode, taking into account the magnification of objects. Structural changes at each stage of the study were analyzed in 50 fields of view on an area of ​​0.1 mm² of the studied sample. The obtained data were evaluated using parametric and nonparametric statistical methods. It was established that on the 70th day of experimental streptozotocin-induced diabetes, the average amount of pancreatic islets per 1 mm2 probably decreases compared to control indicators and is (4.62±0.19) (р<0.05). The area of ​​islets decreases to (5956.84±547.35) μm2 (p<0.001), the same trend is characteristic of B-cells, the number of which decreased to (19.7±0.41) per 0.1 mm². It is experimentally proven that under conditions of diabetes mellitus there is a morphofunctional transformation of the parenchyma of the islets of the pancreas, manifested by the ultrastructural restructuring of the existing B cells, in which the nuclei change: they acquire small size, blurred contours due to the thinning up to the disappearance of the perinuclear space, a large amount of condensed chromatin in which a significant number of small vesicles is detected. The amount of condensed chromatin directly depends on the number of secretory granules in the cytoplasm - the more granules, the more condensed chromatin and the smaller the size of the nucleus. Thus, the introduction of streptozocin causes irreversible changes in the islets of the pancreas, namely their cellular composition decreases by 21%, which is mainly due to a decrease in the number of Insulin cells. Along with this, existing cells are reconstructed in the direction of increasing their functional activity.